Statistical investigation for cutting force and surface roughness of S45C steel in turning processes by I-kazTM method - Samin, R.; Nuawi, M. Z.; Haris, S. M.; Ghani, J. A. (Institute of Physics Publishing, 2020)
This paper presents a statistical analysis to investigatethe correlation between cutting forces and surface roughness values in turning process. Although the correlation of machining processes has been widely studied in metal cutting, it still presents a challenge as surface roughness has to be considered for product quality and it is hard to ensure that this requirement will be achieved. The paper also presents a statistical analysis of signal processing from the force signal in time domain. The cutting force was measured during machining using Kistler 9129AA dynamometer to monitor the force signals and the data was analysed using statistical methods such as skewness, kurtosis and I-kazTM method. The statistical methods were used to data analysis to assess the effect of force signals during the machining process. The results show that the relationship between I-kaz coefficients (Ƶ∞) from the I-kazTM method and surface roughness values (Ra and Rz) can be considered very highly correlated.